Effects of an acute D2-dopaminergic blockade on the somatosensory cortical responses in healthy humans: evidence from evoked magnetic fields - Huttunen, Juha; Kähkönen, Seppo; Kaakkola, Seppo; Ahveninen, Jyrki; Pekkonen, Eero (Neuroreport, 2003)
We tested the possible role of dopaminergic activity in the processing of somatosensory afferent information in healthy humans. Somatosensory evoked magnetic fields (SEFs) were recorded in seven subjects in response to left median nerve stimulation. SEFs were obtained in all subjects after oral administration of 2 mg haloperidol, an antagonist to dopaminergic D2 receptors, and placebo, which were given in a randomized, double-blind cross-over design. SEFs were analyzed using a multiple equivalent current dipole (ECD) model, with one dipole at the right primary somatosensory cortex (SI) and at both left and right secondary somatosensory cortices (SII). The earliest responses from SI, peaking at about 20 ms (N20m) and 35 ms (P35m), were not affected by haloperidol. A later deflection peaking at about 75 ms (P60m), however, was slightly reduced (p < 0.05). Responses arising from SII were not significantly changed. The results suggest that dopaminergic activity may be involved in modulating somatosensory processing after the initial stages of cortical activation.